Cell-Penetrating Peptide and Transferrin Co-Modified Liposomes for Targeted Therapy of Glioma - Xi Wang; Yarong Zhao; Shiyan Dong; Robert J. Lee; Dongsheng Yang; Huan Zhang; Lesheng Teng (Molecules, 2019)
Glioma is one of the most aggressive and common malignant brain tumors. Due to the presence of the blood-brain barrier (BBB), the effectiveness of therapeutics is greatly affected. In this work, to develop an efficient anti-glioma drug with targeting and which was able to cross the BBB, cell-penetrating peptides (R8) and transferrin co-modified doxorubicin (DOX)-loaded liposomes (Tf-LPs) were prepared. Tf-LPs possessed a spherical shape and uniform size with 128.64 nm and their ξ-potential was 6.81 mV. Tf-LPs were found to be stable in serum within 48 h. Uptake of Tf-LPs in both U87 and GL261 cells was analyzed by confocal laser scanning microscopy and by flow cytometry. Tf-LPs were efficiently taken up by both U87 and GL261 cells. Moreover, Tf-LPs exhibited sustained-release. The cumulative release of DOX from Tf-LPs reached ~50.0% and showed excellent anti-glioma efficacy. Histology of major organs, including brain, heart, liver, spleen, lungs and kidney, and the bodyweight of mice, all indicated low toxicity of Tf-LPs. In conclusion, Tf-LPs showed great promise as an anti-glioma therapeutic agent.